Gambaran persalinan letak sungsang di RSUP Prof. Dr. R. D. Kandou Manado - Putra, Bonatua A.; Suparman, Eddy; Tendean, Hermie M.M. (e-CliniC, 2016)
Abstract: Breech presentation is lengthwise position of fetus in the womb with its head is in the fundus. Causes of breech presentation are unknown, however, there are some risk factors, among others: uterine abnormality, gemelli, easily movable fetus (in multiparous, hidramnion, premature), and head fixation on the pelvic brim is not good enough or no fixation at all (in narrow pelvis, hydrocephalus, or anencephaly cases). This study aimed to obtain the profile of breech delivery. This was a descriptive retrospective study using medical records at Prof. Dr. R. D. Kandou Hospital Manado period January-December 2014. The results showed that of the total 3347 labors, there were 152 cases of breech delivery (2.2%). The highest percentages were as follows: multiparous mothers (64.5%); maternal age >35 years (28.9%); 37-40 weeks of gestation (78.3%); complete breech (66.4%); and perabdominal labor (78.3%). Birth weights were mostly in the range of 2500-3500 grams (65.1%) with Apgar scores 4-6 (61.2%). Keywords: breech delivery. Abstrak: Letak sungsang adalah janin yang letaknya memanjang (membujur) dalam rahim, kepala berada di fundus dan bokong di bawah. Penyebab terjadinya letak sungsang tidak diketahui, tetapi terdapat beberapa faktor risiko antara lain: kelainan uterus, gemeli, janin mudah bergerak (pada multipara, hidramnion, prematur), dan fiksasi kepala pada pintu atas panggul tidak baik atau tidak ada (pada panggul sempit, hidrosefalus, anensefali). Penelitian ni bertujuan untuk mendapatkan gambaran persalinan letak sungsang. Jenis penelitian ialah retrospektif deskriptif melalui rekam medik di RSUP Prof. Dr. R. D. Kandou Manado periode Januari – Desember 2014. Hasil penelitian mendapatkan 152 kasus persalinan letak sungsang yaitu sebesar 2,2% dari total 3347 persalinan. Persentase tertinggi ditemukan pada ibu multipara (64,5%); usia ibu >35 tahun (28,9%); usia kehamilan 37-40 minggu (78,3%); complete breech (66,4%); persalinan perabdominal (78,3%). Berat badan lahir bayi letak sungsang terbanyak pada rentang 2500-3500 g (65,1%) dengan nilai apgar terbanyak pada nilai 4-6 (61,2%). Kata kunci: persalinan letak sungsang